Phenolics Profile and Antioxidant Activity Analysis of Kiwi Berry (Actinidia arguta) Flesh and Peel Extracts From Four Regions in China - Zhang, Jiyue; Gao, Ningxuan; Shu, Chi; Cheng, Shunchang; Sun, Xiyun; Liu, Changjiang; Xin, Guang; Li, Bin; Tian, Jinlong (Frontiers in Plant Science, 2021)
The kiwi berry (Actinidia arguta) has been widely concerned by researchers due to its rich phenolics, flavonoids, and vitamin C. Numerous reports have demonstrated that fruit peels contain higher phenolic content and antioxidant activity than that of flesh. In this work, the phytochemical contents and antioxidant activities of peel and flesh extracts of six kiwi berry were analyzed, which are from four regions (Dandong, Benxi, Taian and Tonghua) of China. The antioxidant activity was determined by the peroxyl radical scavenging capacity (PSC) and cellular antioxidant activity (CAA) assays. The experimental results showed that the phenolic, flavonoid and vitamin C contents of kiwi berry peel was up to 10.77, 13.09 and 10.38 times richer than that of kiwi berry flesh, respectively. In addition, the PSC and CAA values of kiwi berry peel are higher than that of kiwi berry flesh. The contents of ten phenolics were determined by HPLC-PDA-MS, the results illustrated that protocatechuic acid, caffeic acid, chlorogenic acid and quinic acid are major phenolics. In conclusion, this study indicated that kiwi berry peel contained rich source of antioxidants deserve. Perhaps, it is of great significance for the full development and utilization of kiwi berry in four regions of China to produce nutraceutical and functional foods.